Actors and resources of an evolving local system. The processes that involve Catania, a dynamic reality in a low developed region - Vittorio Ruggiero; Luigi Scrofani (European Regional Science Association (ERSA), 2001)
Since the second half of the '70s, a great crisis has hit the local system of Catania, - which is the most important town in the North-east of Sicily - both in its economical aspects and in its social and political ones. In the '90s, nevertheless, the city has been interested by deep transformations which have caused new actors and innovative resources to emerge. During the years of crisis, the Catania local system was based on the building industry and on the public expenditure that have nourished clientelistic and also illegal activities. In fact the public expense played a very important role in the economic development of Sicilian society, where most of the industrial enterprises worked in protected sectors. A few exceptions regarded SMEs with innovative capabilities and larger firms depending from an exogenous management. From this point of view, the authors of this paper will try to draw a clear picture of the changes happened in the last decade in the Catania socio-economic system, pinpointing its ability of nourishing new initiatives in high technology sectors and attracting others from the outside, thanks to the new political atmosphere present in the city and its ambitious aspiration to became an important node in the Mediterranean Basin. Some of the actors of these changes are a group of innovative entrepreneurs, the local University and a new class of politicians more sensitive to the economic and social development of the community.
Keywords: 330